Targeted Sequencing Suggests Wild-Crop Gene Flow Is Central to Different Genetic Consequences of Two Independent Pumpkin Domestications - Kates, Heather R.; Anido, Fernando López; Sánchez-de la Vega, Guillermo; Eguiarte, Luis E.; Soltis, Pamela S.; Soltis, Douglas E. (Frontiers in Ecology and Evolution, 2021)
Studies of domestication genetics enrich our understanding of how domestication shapes genetic and morphological diversity. We characterized patterns of genetic variation in two independently domesticated pumpkins and their wild progenitors to assess and compare genetic consequences of domestication. To compare genetic diversity pre- and post-domestication and to identify genes targeted by selection during domestication, we analyzed ~15,000 SNPs of 48 unrelated accessions, including wild, landrace, and improved lines for each of two pumpkin species, Cucurbita argyrosperma and C. maxima. Genetic diversity was reduced in only one domesticated subspecies, C. argyrosperma ssp. argyrosperma, relative to its wild progenitor, and the two domesticated species also have different patterns of genetic structure across domestication status. 1.5% of the domestication features identified for both species were shared between species. These findings suggest that ancestral genetic diversity, wild-crop gene flow, and domestication practices shape the genetic diversity of two similar Cucurbita crops in different ways and add to our understanding of how the reduction of genetic diversity during the processes of domestication and trait improvement impacts the breeding potential of modern crops.